Essential fatty acids : sources, processing effects, and health benefits - Dhull, Sanju Bala; Punia, Sneh; Sandhu, Kawaljit Singh (Boca Raton, FL : CRC Press, 2021)
"Essential Fatty Acids: Sources, Processing Effects, and Health Benefits provides a systematic introduction and comprehensive information about the essentiality of diets rich in omega fatty acids for successful human growth, development and disease prevention. This book presents detailed knowledge about essential fatty acids, their different food sources, biochemistry, and metabolism. It provides a comprehensive assessment of current knowledge about the effects of various processing and storage conditions on essential fatty acids, their bioavailability and supplementation in foods and diet. Chapters highlight the contribution of essential fatty acids in prevention and improvement of various conditions such as heart problems, arthritis, cancer, brain and bone health, especially in developing fetuses and children"--
OCLC-licensed vendor bibliographic record.
Keywords: Fatty acids in human nutrition; Fatty acids -- Health aspects; Fatty acids -- Physiological effect; Essential fatty acids